Revitalizing Local Wisdom for Religious Moderation: A Study of the Babarit Tradition in West Java - Andriani, Sarina; Pallawagau, Baso; Nuur, Khaerun Nisa; Hamzah, Nur Afifah; Aditya, Alfikri Rausen (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2025)
The diversity of religions and beliefs in Indonesia is part of a rich culture that needs to be preserved. In Babakanmulya village, West Java, there is a unique tradition called “Babarit” that combines the celebration of the Islamic New Year with a harvest thanksgiving ceremony. This tradition involves all elements of society regardless of religious and ethnic backgrounds, functioning as a unifier and glue for social harmony. This study aims to analyze the values of religious moderation in Babarit activities in the village. Using a qualitative approach with analytical descriptive methods, this research reveals the meaning and philosophy of Babarit implementation and its role in maintaining inter-religious harmony. The results show that the Babarit tradition contains religious moderation values such as tolerance, justice, balance between tradition and religious teachings, mutual cooperation, and strengthening social harmony. This activity not only strengthens solidarity between residents, but can also be a model for the development of religious moderation values in other areas. This research suggests further study of the impact of Babarit on cultural and religious identity and its role as a model for religious moderation in other communities in Indonesia.